2020
DOI: 10.1101/2020.04.20.052399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Candida aurisphenotypic heterogeneity determines pathogenicityin vitro

Abstract: 1Candida auris is an enigmatic yeast that provides substantial global risk in 2 healthcare facilities and intensive care units. A unique phenotype exhibited by 3 certain isolates of C. auris is their ability to form small clusters of cells known as 4 aggregates, which have been to a limited extent described in the context of 5 pathogenic traits. In this study, we screened several non-aggregative and 6 aggregative C. auris isolates for biofilm formation, where we observed a level of 7 heterogeneity amongst the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…They get exposed to multiple broad spectrum antibiotics, antifungals and antiseptics [80,83]. All of these factors dramatically alter the normal host microbiota, creating favourable conditions for C. auris to colonize and invade [84]. Could the expansion of such dense clusters of susceptible hosts have possibly reached a tipping point in tandem with the changes in the environment, to allow C. auris to emerge as an efficient nosocomial pathogen?…”
Section: Host-pathogen-environmental Factors and Tipping Pointsmentioning
confidence: 99%
“…They get exposed to multiple broad spectrum antibiotics, antifungals and antiseptics [80,83]. All of these factors dramatically alter the normal host microbiota, creating favourable conditions for C. auris to colonize and invade [84]. Could the expansion of such dense clusters of susceptible hosts have possibly reached a tipping point in tandem with the changes in the environment, to allow C. auris to emerge as an efficient nosocomial pathogen?…”
Section: Host-pathogen-environmental Factors and Tipping Pointsmentioning
confidence: 99%
“…Although relatively little is known about how C. auris colonizes and causes disease, it is quite evident that this novel pathogen is strikingly distinct among yeasts ( 35 , 36 ). One unique growth feature in some isolates is cell aggregation ( 17 ) which was associated in vitro with differences in drug susceptibility, biofilm formation, and adhesin expression compared to nonaggregative isolates ( 1 , 11 , 14 , 17 , 32 ). Since previous studies have reported variable results for the biofilm-forming abilities of these isolates ( 14 , 17 , 18 ), we comparatively evaluated the 10 C. auris isolates in the CDC panel and selected the highest (0382-HBF) and lowest (0387-LBF) biofilm-forming isolates as phenotypic representatives for subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pathirana et al ( 18 ) found that strain 0382-HBF is able to survive inside neutrophils significantly better than C. albicans , whereas strain 0387-LBF was susceptible to neutrophil killing. Additionally, unique fungal recognition and/or host profiles to different C. auris phenotypes were also reported using an in vitro skin wound model ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations